Intermodal logistics in the state of Rio Grande do Norte: an exploratory study (Research, Society and Development, 2018)
This paper aims to present the obstacles and challenges for the development of logistic integration in the state of Rio Grande do Norte. For this, an exploratory study was carried out with the use of the content analysis technique in which three professionals were interviewed who work or have already worked directly with the road, sea and air modalities within the state and who are experts in the area, being made the analysis of the theoretical convergence with the speeches of the subjects. As a result, it was obtained that the poor infrastructures of access and pathways to reach the port and airport are the main obstacles for intermodality followed by the lack of the modal rail for the movement of cargoes within the state of Rio Grande do Norte.